ANALISIS SEMANTIK UMUM : PEMBERITAAN TERORIS “IMAGE ISLAM”PADA MAJALAH TEMPO DAN SABILI - Rahma Hidayati (Universitas Teuku Umar, 2016)
People tend to misconceive the word terrorist thereby equating with Islam. There are several labels and inferences given on the word terrorist such as radical, militants, extreme etc. Thus this study was conducted to analyze the image of Islam and terrorists in Tempo and Sabili magazines. Qualitative methodology was used to conduct this research, namely, content analysis. Data obtained were analyzed using sub-categories trikotomi from the General Semantic perspectives forwarded by Rajib Ab Ghani (1984). Both Tempo and Sabili tend to use unsourced inferences in their report. Keywords: Image of Islam, General Semantic Analysis